MUSIC BELONGS TO ALL OF US! EVEN TO THE DEAF! (?) - GYÖRGYJAKAB, Miklós (Studia Universitatis Babes-Bolyai Musica, 2018)
We are all different when it comes to the perception modality we prefer when getting to know the world around us. The deaf cannot hear the music, but they can see and feel it if we provide them with the right visual (sight) and tactile/kinaesthetic (touch/movement) elements. For the first time in Romania, we implemented a unique musical project for the deaf and hearing-impaired people of Transylvania. The events were locally based, but were organized in several cities, so deaf people could literally feel and enjoy the wonderful world of music. Thanks to partnerships with various public and private institutions (among which there were schools, philharmonics, choirs, church communities, NGOs), the events were organized without a financial involvement of the deaf people from Transylvania, who also benefited from the services of several sign language interpreters.